Facilitating Action Learning a practitioner's guide - Pedler, Mike. (New York Open University, 2013)
Action Learning is based on the simple idea that leaders and managers learn best by working together in a group, helping each other find solutions to real work problems through discussions. Facilitating Action Learning is a clear, concise and straightforward guide to this well-established leadership and management development technique.
Index
Keywords: Learning